WALKABILITY STUDY IN THE RAWA BUNTU STATION AREA, SOUTH TANGERANG - Dewi Saraswati; Anindita Ramadhani; Wisely Yahya (Universitas Trisakti, 2024)
Rawa Buntu Station is the second most populous city in Tangsel City. This causes a shift in users coming from Tangsel City to DKI Jakarta or from DKI Jakarta to Tangsel City. There are so many users that there are crowds in the morning and afternoon, this is because space in the Rawa Buntu Station Area is very limited. The aim of this research is to determine the level of walkability in the Rawa Buntu Station Area, South Tangerang. The quantitative descriptive analysis method uses the Global Walkability Index which is measured through the level of walkability from the results of observations and questionnaires of users in the Rawa Buntu Station Area. Based on the results of the analysis, the assessment of the level of walkability in the three segments of the Rawa Buntu Station Area has a score in segment 1 of the Rawa Buntu Station access road, which is 62.71, which means moderate, in segment 2, the Rawa Buntu Station access road, which is 61.92, which means moderate. , and on section 3 of Palangka Raya road it was 61.92, which means medium.In the Rawa Buntu Station area, there are observation results where the majority of pedestrian route users have a level of security and safety in using infrastructure that is still minimal, this is because BSD residents use more transportation in the center of Serpong Station compared to transit stations, in general the level walkability is moderate. Based on the results of observations and respondents, there are still several problems withpedestrian facilities in the Rawa Buntu Station Area, such as damage to several sidewalk structures at several points with cracks or holes, side obstacles such as street vendors (PKL) and online motorcycle taxis which have an impact on disruption. space for pedestrians and bicycle users around the station. Pedestrian development using TOD principles in the Rawa Buntu Station Area has been planned in the Regional SpatialPlanning (RTRW) where these principles prioritize pedestrians, but this development has not been implemented. So, overall the level of walkability in the Rawa Buntu Station area has a moderate score, which means there are several aspects that need to be improved in the Rawa Buntu Station area.